Effect of incremental levels of apple pomace and multi enzyme on performance, immune response, gut development and blood biochemical parameters of broiler chickens - Amir Hosein Aghili; Majid Toghyani; Sayed Ali Tabeidian (International Journal of Recycling of Organic Waste in Agriculture)
Purpose During the apple processing procedures, a large amount of apple pomace is generated which is contains peel, core, seed, calyx, stem, and soft issue. The polyphenolic compounds in apple pomace are strong antioxidants that are able to counterbalance the free radicals; also, it is a rich source of many nutrients such as carbohydrates, minerals, fiber except protein. The experiment was conducted to investigate the effect of different levels of dried apple pomace in broilers diet. Methods The incremental levels of dried apple pomace (4, 8, 12, 16 and 20%) with and without enzyme were used in broilers diet (8 dietary treatments). The growth performance, immune response, gut development, antioxidant capacity (TAC) and blood biochemical parameters were evaluated. Results The lowest daily weight gain, body weight and poorest feed conversion ratio was obtained by F treatment (Pâ<â0.05), enzyme inclusion along with dried apple pomace had positive effect on growth performance. The antibody titter against Newcastle, Influenza and SRBC was increased by C, H, G and H treatments, respectively (Pâ<â0.05). Antibody titer against NDV, IDV, and SRBC by 4, 8, 12 and TAC by 12, 16 and 20% of dried apple pomace significantly increased. The villous height by 4, 8, 12 and crypt depth by 12, 16 and 20% dried apple pomace significantly and insignificantly decreased, respectively. Conclusion The results suggested that the incremental levels of dried apple pomace deteriorate growth performance, modified antibody titer production, total antioxidant capacity and blood parameters of broilers.